TOURIST FLOWS OF KAZAKHSTAN: STATISTICS, GEOGRAPHY, TRENDS - Belgibayeva, Zh.Zh.; M. Nadyrov, Sh.; Zhanguttina, G.O.; Belgibayev, A.K.; Belgibayev, A.A. (Scientific Journal of Pedagogy and Economics, 2020)
The article covers the issues related to the study of the tourist flow as a population of people temporarily moving to Kazakhstan and traveling from Kazakhstan abroad for tourism. The problems of accounting and analysis of tourist flows occupy a central place in the tourism economy and are still polemical. During the research, the following results were obtained: firstly, the tourist flow as an economic indicator, notion, and process was investigated; secondly, the analysis of tourist flows in terms of structural changes, dynamics, geographical signs; thirdly, the growth prospects of inbound tourist flows based on the results of the SWOT analysis were justified.